E-Commerce Tax Implementation: A Study on South Korean Product Online Shop Business - Zahirah, Zahirah; Pramukti, Andika; Arsyad, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the understanding of e-commerce taxation among Indonesian entrepreneurs selling South Korean products online. The growing demand for South Korean goods has driven entrepreneurs to use e-commerce platforms to efficiently reach out to physical interactions. Research Design and Methodology: This research adopted a qualitative descriptive approach. Primary data were collected through Google Forms and virtual interviews with a sample of online store owners. This method allowed a deeper understanding of the participants' perspectives on e-commerce tax issues. Findings and Discussion: The study found that while some online shop owners are familiar with e-commerce tax regulations, others remain unaware due to a lack of socialization from tax authorities. The absence of clear communication about tax obligations creates a knowledge gap, leading to inconsistent compliance among business owners. Implications: This research emphasizes the need for better tax education and socialization to improve compliance and support the growth of e-commerce in Indonesia. The findings suggest that tax authorities should focus on targeted outreach programs to ensure online store owners are well-informed about their tax obligations. This study contributes valuable insights for policymakers to enhance regulatory frameworks for e-commerce taxation.